2019
DOI: 10.1093/tas/txz147
|View full text |Cite
|
Sign up to set email alerts
|

Diet formulation method influences the response to increasing net energy in finishing pigs1

Abstract: An experiment was conducted to compare the effects of increasing dietary net energy (NE) in finishing pig diets while either maintaining a standardized ileal digestible lysine:NE ratio (SID Lys:NE) or maintaining SID Lys as a constant percentage of the diet across increasing energy densities. A total of 150 pigs (Line 600 × 241; DNA, Columbus, NE; initially 35.7 kg) were used in a 91-d study. Pigs were blocked by sex and weight and randomly assigned to 1 of 5 treatments with 2 pigs per pen and 15 pens per trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Other studies have also reported improvements in caloric efficiency when dietary NE is reduced [26,41,42]. The unexpected effect on NEE might be attributed to an additional effect of fibrous ingredients, such as wheat middlings, by limiting physical satiety [13,43] or to an underestimation or overestimation of the NE value of some ingredients [26,36]. For instance, Kil et al [44] reported low NE values for animal fat (5.90 Mcal/kg) compared to this study (7.56 Mcal/kg).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Other studies have also reported improvements in caloric efficiency when dietary NE is reduced [26,41,42]. The unexpected effect on NEE might be attributed to an additional effect of fibrous ingredients, such as wheat middlings, by limiting physical satiety [13,43] or to an underestimation or overestimation of the NE value of some ingredients [26,36]. For instance, Kil et al [44] reported low NE values for animal fat (5.90 Mcal/kg) compared to this study (7.56 Mcal/kg).…”
Section: Discussionmentioning
confidence: 93%
“…1 as a reference, increasing SID Lys had a greater impact on the SID Lys:NE ratio than reducing NE (0.79 vs. 0.34 g/Mcal). On the contrary, Marçal et al [26] showed no effect of NE on ADG when diets were formulated with the same SID Lys and not based on SID Lys:NE. However, as in the present study SID Lys was formulated for the high NE diet, SID Lys intake was even higher in the low NE diets.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations